FORMING STUDENT CHARACTER THROUGH THE ISLAMIC BOARDING SCHOOL PROGRAMS AT SMP-IT TARBIYATU BANIN DUKUHPUNTANG CIREBON - Muthoharoh; Inez Elvina (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
Education is an effort to shape students' characters, one of which is to develop students who are independent, cooperative, tolerant, and critical thinkers. The purpose of this qualitative descriptive study is to collect data on the process and application of character education, as well as data about the difficulties that teachers face when implementing character education in Islamic boarding schools. This study included several respondents, including Islamic boarding school supervisors, school principals, teachers, and eighth grade students. Interviews, observation, and documentation were used to obtain and collect data on character education in Islamic boarding schools. The results of this research demonstrate that character education at the Islamic Boarding School Tarbiyatul Banin Dukuntang Cirebon is consistent with national education goals, namely character formation. According to the data, the character education implemented at Tarbiyatul Banin Integrated Islamic Junior High School, Dukupuntang, Cirebon uses the implementation of programs provided at schools and also at boarding schools such as the dhuha prayer program, fardhu prayer in congregation, tahajjud prayer, and dhikr in the form of istighfar to build the students' religious character. extracurricular activities, cults to develop student leadership and self-confidence, programs such as Qur'an translation, Tahfidz, and book recitation to explore religious knowledge.